The effect of differentiated learning using the PBL model on students' ability to understand mathematical concepts - Ambarini, Tasya; Izzati, Nur; Siregar, Nur Asma Riani (Jurnal Pengembangan Pembelajaran Matematika (JPPM), 2024)
Understanding mathematical concepts (PKM) is crucial and needs to be achieved first by students so that they can understand the material they are studying well and can learn advanced material. The results of the initial study at SMA Negeri 6 Tanjungpinang showed that students had not been able to master mathematical concepts well. Implementing differentiated learning combined with the problem-based learning (PBL) model is a solution teachers can offer to overcome student problems. This research aims to determine the effect of differentiated learning using the PBL model on students' PKM abilities at SMA Negeri 6 Tanjungpinang. A quasy experimental with a non-equivalent control group design was applied in this research. The research samples were classes X.1 and X.2, selected from all class X SMA Negeri 6 Tanjungpinang through cluster sampling techniques. Pretest-posttest was chosen as the data collection technique. Data were analyzed using an independent sample t-test with a significance level of 5%. The results of the research show that differentiated learning with the PBL model has a significant influence on students' PKM abilities.